Study of the Secondary Flow Formed on Two-Channel Junction Using Computational Fluid Dynamics - Pratiwi, Tasya Mahardika; Putra, Yoga Satria; Sampurno, Joko; Muhardi, Muhardi; Sutanto, Yuris (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2024)
Information about the secondary flow formed at the junction is crucial for identifying areas vulnerable to erosion. This study aims to build a water flow simulation at a two-channel junction with varying angles using Computational Fluid Dynamics (CFD). The goal of the simulation is to analyze the velocity changes on each variation of angles (90°, 70°, 50°, 30°, and 10°) on the two-channel junction. The validation of these flow patterns is significantly connected to the reference data. The secondary flow is formed as the impact of the velocity changes, and the main channel flow meets the branch channel flow. The flow patterns at the 90° junction exhibit similar formation, as evidenced by secondary zones formed around the junction, such as the contraction and separation zones. The contraction zone forms in areas near junctions with high-velocity values, while the separation zone develops in areas where velocity decreases due to the impact of two flows. This study found that CFD effectively analyses velocity changes on two-channel junctions.